Ageing with an intellectual disability: the impact of personal resources on well‐being. (14th September 2012) - Lehmann, B. A.; Bos, A. E. R.; Rijken, M.; Cardol, M.; Peters, G.‐J. Y.; Kok, G.; Curfs, L. M. G.
Abstract Background The population of ageing people with mild and moderate intellectual disabilities (ID) is growing rapidly. This study examines how personal resources (physical health, mental health and social networks) impact the well‐being of ageing people with ID. Methods Longitudinal survey data on 667 people with a mild or moderate ID were acquired via interviews in 2006 and 2010. Indicators of personal resources (physical health, mental health and social networks) were assessed, as were indicators of well‐being (satisfaction with life, happiness and loneliness). Additionally, data on background characteristics and autonomy were gathered. Results The results show that age is positively related to decreased mobility and auditory disabilities and negatively related to independent living, autonomy in how one spends one's leisure time and autonomy in decision‐making. Longitudinal analyses demonstrated that, with the exception of health that deteriorated, and social satisfaction that improved, almost all variables remained stable over the 4‐year period. Further, good physical health in 2006 predicted happiness in 2010. Conclusion Despite the fact that age is associated with poorer physical and mental health and a smaller social network, this study showed that older people with ID have relatively high levels of well‐being. Findings are discussed in the light of coping with ageing and impact of life events.